2002
DOI: 10.1021/ja020682l
|View full text |Cite
|
Sign up to set email alerts
|

Dianionic Tetraborates Do Exist as Stable Entities

Abstract: To date, B(6)H(6)(2-) and some of its derivatives are the smallest members of the closo-borates that have been synthesized and analyzed in condensed phases. In contrast, no stable dianionic tetraborate has yet been observed, either in solution or solids or in the gas phase. In this work, the gas-phase stability of dianionic tetraborates B(4)X(4)(2-) (X = H, CN, NC, or BO) is investigated with ab initio methods. For this objective, the geometries of the dianions are optimized, the electronic stability is tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The B n H n 2À (n ¼ 6-12) and (n ¼ 4, 5, 13-17) have been observed experimentally and investigated theoretically, respectively. [51][52][53][54][55]81,82 In order to grasp the structural features and assure the integrity in this family, B n H n 2À with n ¼ 2 and 3 are considered as well. The structures of borane dianions are taken from the previous studies of Lipscomb, Schleyer, Dreuw, and their co-workers.…”
Section: Geometries and Stabilitymentioning
confidence: 99%
“…The B n H n 2À (n ¼ 6-12) and (n ¼ 4, 5, 13-17) have been observed experimentally and investigated theoretically, respectively. [51][52][53][54][55]81,82 In order to grasp the structural features and assure the integrity in this family, B n H n 2À with n ¼ 2 and 3 are considered as well. The structures of borane dianions are taken from the previous studies of Lipscomb, Schleyer, Dreuw, and their co-workers.…”
Section: Geometries and Stabilitymentioning
confidence: 99%
“…6,8 Inspired by the theoretical results on C 4 H 2− 4 , homo-, 1,3-heteronuclear, and inorganic four-memberedring systems with 6π electrons were studied to determine their structure, stability, and aromaticity. 9, 10 The planar cyclotetraphosphide (P 2− 4 ) structure has been confirmed by experiment and theory, and is considered to be aromatic. 11 Recently, the (SiR) 2− 4 dianion has been found as a new ligand for transition metal complexes.…”
Section: Introductionmentioning
confidence: 93%
“…studied the stability of B 6 H 6 2− by substituting the H atoms with groups such as F, Cl, CN, NC or BO, which resulted in stable dianions in the gas phase . Similar studies have also been performed for the penta‐ and tetraborate dianions B 5 X 5 2− and B 4 X 4 2− . The role of substituents in enhancing the stability of multiply charged species in the gas phase was recently studied by substituting H atoms in B 12 H 12 2− by CN moieties.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Similar studies have also been performed for the penta-and tetraborate dianions B 5 X 5 2À and B 4 X 4 2À . [9,10] The role of substituents in enhancing the stability of multiply charged speciesi nt he gas phase was recently studied by substituting Ha toms in B 12 cluster was found to be unusually stable with the second electron bound by 5.3 eV,w hich is almost six times largert han that in the B 12 H 12 2À dianion. [11] The powero fs ubstituent engineering was further demonstrated when aBatom in the cage was replaced by aCatom, to form CB 11 (CN) 12 2À .I tw as found that CB 11 (CN) 12 2À is also stable, whereas its isoelectronic analogue CB 11 H 12 2À is unstable.…”
Section: Introductionmentioning
confidence: 99%